Habituation of Society in Fulfilling Economic Needs Through Digital Media During the Covid-19 Pandemic in Surabaya, East Java - Rohmah, Ichmi Yani Arinda; Amelia, Riska (Indonesian Journal of Digital Society is a scientific journal, 2020)
Surabaya is one of the big cities in East Java Province, Indonesia. During the Covid-19 pandemic, the city was included in the category of cities with the number of patients infected with Covid-19 which was quite high, second only to Jakarta. Since the covid-19 pandemic, the people of Surabaya have been faced with conditions that require people to be more anticipated by the spread of covid-19. There are a number of new health protocols imposed by the government on the public. In addition, the Surabaya local government has also imposed a Large-Scale Social Restriction (PSBB) regulation as an effort to prevent the spread of the Covid-19 pandemic. The existence of a number of these regulations encourages the community to adapt and implement the rules well. Restrictions on the space for movement in the public encourage people to be able to find strategies to continue to be active in meeting economic needs. In this strategy, the community uses digital media to meet economic needs. Based on these social phenomena, researchers conducted research using qualitative research methods. Data collection techniques using interview techniques and non-participant observation. The research was conducted for approximately two months and is located in the city of Surabaya. The results showed that there were new adaptations for society in meeting economic needs during the Covid-19 pandemic. This adaptation is carried out by utilizing digital media and implementing health protocols properly in meeting economic needs. In the adaptation process until it becomes a new habit for the community, it is strengthened by the existence of new social, economic and cultural capital that can encourage people to meet economic needs during the Covid-19 pandemic. Keywords : Habituation, economic needs, digital media, Covid-19 pandemic